Developing a legal assistant website â€œNotoaturanâ€ using Waterfall method - Utami, Melinda; Zen, Bita Parga; Rauna, Yayi Sufia (Politeknik Ganesha Medan, 2021)
The development of increasingly advanced technology brings great benefits to people's lives. This is evidenced by the many uses of technology in various fields of life. The development of information technology also affects people's behavior which shows a new phenomenon where several activities can be carried out online to make it more effective and efficient. This also happens in the field of law, with the term e-legal services. The process of digitizing legal services can be realized if there is good support from the government, legal service providers, and the community. The government itself has provided laws and regulations that discuss legal digitization. Data and information are collected in two ways, interviews and literature study. By using the waterfall software development method, the Notoaturan website is built using the PHP programming language, with the Codeigniter 3 framework with MySQL database. The results obtained are in the form of a notoaturan website that provides services related to notaries and lawyers. Notary provides a process for ordering notary services such as creating a business entity, creating a CV, making a PT, and others, as well as providing services for placing an order for a lawyer starting with prior consultation. The website is also equipped with several additional services such as complaints and assistance for using the website.